Implementation of a Web-based Geographic Information System for Mapping Rabies Cases in the Indonesia – Timor Leste Border Area - Yulianti Paula Bria; Donatus Joseph Manehat; Yovinia Carmeneja Hoar Siki; Philipus Pratama Putra Balla; Jaime da Costa Lobo Soares; Apolinario dos Santos (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2026)
The high spread of rabies in Malaka Regency has raised concerns among the people of Malaka, including communities in Timor Leste that directly border the regency. Information about the spread of this disease has not been openly disseminated to the public due to the absence of a system capable of accommodating such needs. To address this problem, it is necessary to develop a Geographic Information System (GIS) for mapping rabies cases in the Indonesia - Timor Leste border area. The system is developed as a web-based platform, enhancing accessibility by enabling residents to retrieve information from any location with internet access. The project was carried out in three primary phases: preparation, deployment, and testing and evaluation. The development and implementation of the system were completed successfully. The findings indicate that the developed system functions effectively as an information tool for the community. Evaluation results demonstrate that it successfully provides accessible and reliable data on rabies cases in Malaka and nearby areas, including bordering districts in Timor Leste. The system achieved an average acceptance score of 4.64, reflecting a generally positive response from users. Overall, the web-based GIS proves to be a practical and efficient solution for improving the delivery and impact of public health information services.